Long-term effectiveness of Self-Help Plus in refugees and asylum seekers resettled in Western Europe: 12-month outcomes of a randomised controlled trial. (8th June 2022) - Turrini, G.; Purgato, M.; Tedeschi, F.; Acartürk, C.; Anttila, M.; Au, T.; Carswell, K.; Churchill, R.; Cuijpers, P.; Friedrich, F.; Gastaldon, C.; Klein, T.; et al.
Abstract: Aims: As refugees and asylum seekers are at high risk of developing mental disorders, we assessed the effectiveness of Self-Help Plus (SH + ), a psychological intervention developed by the World Health Organization, in reducing the risk of developing any mental disorders at 12-month follow-up in refugees and asylum seekers resettled in Western Europe. Methods: Refugees and asylum seekers with psychological distress (General Health Questionnaire-12 ⩾ 3) but without a mental disorder according to the Mini International Neuropsychiatric Interview (M.I.N.I.) were randomised to either SH + or enhanced treatment as usual (ETAU). The frequency of mental disorders at 12 months was measured with the M.I.N.I., while secondary outcomes included self-identified problems, psychological symptoms and other outcomes. Results: Of 459 participants randomly assigned to SH + or ETAU, 246 accepted to be interviewed at 12 months. No difference in the frequency of any mental disorders was found (relative risk [RR] = 0.841; 95% confidence interval [CI] 0.389–1.819; p -value = 0.659). In the per protocol (PP) population, that is in participants attending at least three group-based sessions, SH + almost halved the frequency of mental disorders at 12 months compared to ETAU, however so few participants and events contributed to this analysis that it yielded a non-significant result (RR = 0.528; 95% CI 0.180–1.544; p -value = 0.230). SH + was associated with improvements at 12 months in psychological distress ( p -value = 0.004), depressive symptoms ( p -value = 0.011) and wellbeing ( p -value = 0.001). Conclusions: The present study failed to show any long-term preventative effect of SH + in refugees and asylum seekers resettled in Western European countries. Analysis of the PP population and of secondary outcomes provided signals of a potential effect of SH + in the long-term, which would suggest the value of exploring the effects of booster sessions and strategies to increase SH + adherence.